Nanoencapsulated Petroselinum crispum essential oil: Characterization and practical efficacy against fungal and aflatoxin contamination of stored chia seeds. (August 2021) - Deepika; Chaudhari, Anand Kumar; Singh, Akanksha; Das, Somenath; Dubey, Nawal Kishore
Abstract: The present study explores the practical efficacy of chitosan (CS) nanoemulsion loaded with Petroselinum crispum essential oil (CS-PEO). Since, nanoencapsulation of EO is an emerging field in food science, the PEO was encapsulated into CS nanoemulsion and investigated their efficacy against fungal, aflatoxin B1 ( Af B1 ) contamination and lipid peroxidation of stored Salvia hispanica (chia seeds). The GC/MS analysis of PEO confirmed the presence of carvacrol (48.45%) as the major component. The successful encapsulation of PEO was confirmed through FTIR, XRD, and SEM analysis. During in vitro investigation, CS-PEO completely inhibited the growth of Aspergillus flavus (AF-LHP-SH1) as well as eleven other storage fungi at 1.0 μL/mL and Af B1 production at 0.75 μL/mL. The reduction of cellular ergosterol followed by subsequent release of cellular constituents confirmed plasma membrane as possible target for antifungal mode of action of CS-PEO. The inhibition of methylglyoxal shed light on novel antiaflatoxigenic mode of action. Further, CS-PEO showed remarkable antioxidant activity with IC50 value equivalent to 14.24 μL/mL as measured through DPPH assay. During in situ investigation, CS-PEO completely inhibited the production of Af B1 and lipid peroxidation in treated chia seeds for one year of storage, and exhibited satisfactory safety profile (LD50 = 26, 830 μL/kg body weight) in mammalian model (mice). Based on overall results, it can be concluded that CS-PEO could be recommended for industrial scale application in the management of fungal and aflatoxin mediated loss of stored chia seeds. Graphical abstract: Image 1 Highlights: PEO was encapsulated into CS and characterized by SEM, FTIR and XRD analysis. CS-PEO exhibited enhanced antifungal and antiaflatoxigenic efficacy. CS-PEO retarded Af B1 contamination and lipid peroxidation in chia seeds. CS-PEO exhibited nonphytotoxic nature with high mammalian safety. Nanoemulsified PEO could be recommended as a novel food preservative.